Panama : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper argues that Panama's prospects for maintaining buoyant growth critically depends on continued productivity growth underpinned by comprehensive reforms focused on improving education quality, attracting talent, and continuing to enhance the investment climate. Panama experienced both episodes of growth convergence and divergence over the past several decades. Following a stellar performance in recent decades, Panama's prospects of maintaining high growth rates and moving toward the club of high-income economies critically depends on continued productivity gains. Panama's economy embarked on a path of rapid growth since the political stabilization in the 1990s, which has brought it closer to moving from the middle to the high-income bracket. However, maintaining high growth rates may prove increasingly challenging, particularly for countries at Panama's current level of income. Policies that focus on improving education quality, attracting foreign talent toward knowledge-based sectors of the economy, and strengthening the investment environment are likely to be essential for sustaining productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet